2018
DOI: 10.1371/journal.pone.0202111
|View full text |Cite
|
Sign up to set email alerts
|

The prehospital quick SOFA score is associated with in-hospital mortality in noninfected patients: A retrospective, cross-sectional study

Abstract: This study aimed to determine the accuracy of the quick Sequential Organ Failure Assessment (qSOFA) score in predicting mortality among prehospital patients with and without infection. This single-center, retrospective, cross-sectional study was conducted among patients who arrived via the emergency medical services (EMS). We calculated the qSOFA score and Modified Early Warning Score (MEWS) from prehospital records. We identified patients as infected if they received intravenous antibiotics at the emergency d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Currently, several studies have investigated the performance of the prehospital qSOFA score [1517, 2326]. Vaittinada Ayar P et al have reported that in-hospital mortality rate was significantly higher in patients with prehospital qSOFA positivity among 332 patients suspected with infection (prehospital qSOFA-positive: 41% [55/133] vs prehospital qSOFA-negative: 18% [36/199], p<0.001) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies have investigated the performance of the prehospital qSOFA score [1517, 2326]. Vaittinada Ayar P et al have reported that in-hospital mortality rate was significantly higher in patients with prehospital qSOFA positivity among 332 patients suspected with infection (prehospital qSOFA-positive: 41% [55/133] vs prehospital qSOFA-negative: 18% [36/199], p<0.001) [24].…”
Section: Discussionmentioning
confidence: 99%
“…The qSOFA scores ranged from 0 to 3, with a higher score indicating more severe disease [10][11][12]. The mEWS was calculated from vital signs (RR, heart rate, SBP, and body temperature) and mental status (AVPU) [13,14]. The RTS was calculated by applying a special expression including weights using the same variables as the qSOFA.…”
Section: Variables and Outcomesmentioning
confidence: 99%
“…However, identifying those that are declining into a critically ill state can be challenging 2,3 . In the prehospital environment, early identification of high-risk patients is crucial as it enables early intervention, transportation, and may determine the trajectory of future care 4,5 . There are established ambulance guidelines to diagnose specific conditions such as myocardial infarction, stroke and major trauma.…”
Section: Introductionmentioning
confidence: 99%